(untitled) (International Congress on Economics, Management and Business Studies, 2026)
This paper analyzes the hourly variation of pedestrian flows at a signalized pedestrian crossing that connects two commercial areas on Farobiy Street in the city of Kokand. During the study, pedestrian flows were examined by age groups and the main factors influencing the intensity of movement were identified. The results show that the majority of pedestrians belong to the economically active population, and the peak pedestrian volumes coincide with the busiest trading hours. The obtained findings are practically important for assessing the interaction between pedestrian movement and traffic flow within the urban transport system, as well as for developing management decisions aimed at improving road safety.